-8(-6x-9)=9(-4x-6)
ago in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

-8(-6x-9)=9(-4x-6),

48x+72=-36x-54,

48x+36x=-54-72,

84x=-126,

Divide both sides by 42:

2x=-3, x=-3/2.

CHECK Put x=-3/2 into the original equation:

-8(9-9)=9(6-6), so 0=0 OK.

Another way to solve: rewrite the original equation:

-24(-2x-3)=18(-2x-3) by factorising the contents of the parentheses,

42(-2x-3)=0, so, since 42 is not zero, -2x-3=0, 2x=-3, x=-3/2.

ago by Top Rated User (677k points)

Related questions

0 answers
1 answer
asked Sep 19, 2013 in Algebra 1 Answers by anonymous | 82 views
2 answers
asked Sep 2, 2012 in Geometry Answers by anonymous | 956 views
1 answer
asked Aug 26, 2012 in Algebra 1 Answers by anonymous | 413 views
1 answer
asked Apr 30, 2012 in Algebra 1 Answers by anonymous | 248 views
0 answers
asked Apr 20, 2012 in Pre-Algebra Answers by anonymous | 101 views
1 answer
asked Jan 23, 2012 in Geometry Answers by anonymous | 235 views
0 answers
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
83,564 questions
88,441 answers
1,983 comments
5,511 users